Bridging the gap: from standards to reality in wheelchair headrest-backrest design: a case study. - Aveyard, Benjamin; Dauncey, William; Redwood-Thomas, Jacob; Eggbeer, Dominic; Penman, Russell; Tasker, Lorna (Disability & Rehabilitation: Assistive Technology, 2025)
Purpose: A barrier to the design, manufacture, prescription, testing and evaluation of postural support devices is the lack of user interface force data available. This is in part due to the lack of instrumentation suitable for data collection. This work attempts to address the need for practical instrumentation and record force data. Methods: Instrumentation was developed and used to record real-world unidirectional force data from an individual with high-strength extensor patterns. This data was then used to undertake comparative testing of a custom-made backrest shell using methods described in ISO 16840-3: Wheelchair seating - Part 3: Determination of static, impact and repetitive load strengths for postural support devices. Results: Data collected had a higher magnitude and frequency force than comparative testing forces. This led to a pass and a fail respectively, of the original ISO 16840-3 test and the real-world informed parameters. Conclusion: The data collected highlights the need for better understanding of forces exerted by users on the PSDs. This is especially true of users with complex conditions, behaviours and postures that may exert forces outside of the norm. Developing the correct instrumentation and centring users experiences to inform testing, design and manufacture, prescription of devices and technology evaluations is key to this process.